Hepatic LC3 II/I ratio is not modulated in exercised mice - Marafon, B B; Pinto, A P; da Rocha, A L; Rovina, R L; Pauli, J R; De Moura, L P; Cintra, D E; Ropelle, E R; Da Silva, A S R (Physiological research, 2020)
Autophagy plays an essential role in body homeostasis achievement. One of the main proteins involved in this process is the LC3I, which, after lipidation, leads to the formation of LC3II that participates in the formation and maturation of autophagosome. This descriptive study verified the responses of LC3II to LC3I proteins, as well as the time-course of this ratio in mice livers after different types of acute physical exercise protocols. Eight-week-old male C57BL/6 mice were maintained three per cage with controlled temperature (22±2 °C) on a 12:12-h light-dark normal cycle with food (Purina chow) and water ad libitum. Mice were randomly divided into four groups: control (CT, sedentary mice), resistance (RE, submitted to a single bout of resistance exercise), endurance (EE, submitted to a single bout of endurance exercise), and concurrent (CE, submitted to a single bout of endurance combined with resistance exercise). The mice livers were extracted and used for the immunoblotting technique. The hepatic LC3B II/I ratio for the RE and EE groups were not altered during the different time-points. For the CE group, there was a decrease in this ratio 12h after exercise compared to time 0 and 18h. Also, the hepatic LC3B II/I ratios were not different among the acute physical exercise protocols along the time-course. The hepatic LC3B II/I ratio was not influenced by the endurance and resistance protocols but decreased in response to the concurrent protocol at 12h after the stimulus.
Keywords: játra; signální transdukce; Signal Transduction; Physical Endurance; kondiční příprava zvířat; zvířata; autofagie; myši; myši inbrední C57BL; Mice; fyzická vytrvalost; kosterní svaly; Liver; Male; Muscle, Skeletal; Mice, Inbred C57BL; proteiny asociované s mikrotubuly; Physical Conditioning, Animal; Animals; Autophagy; mužské pohlaví; Microtubule-Associated Proteins